Influence of spatially variable fault friction on tunnel-induced fault stability - T. Mohamed; H. Alhajj Chehade (Results in Engineering)
The activation of fault slip due to the redistribution of stresses after tunnel excavation is a major tunnel hazard. Although the angle of friction of the fault controls the stability, existing methods use deterministic analyses, ignoring its spatial variability. This study proposes a novel coupled analytical-probabilistic framework that integrates an improved Kirsch solution for stress redistribution with spatially random fault friction modeling via Monte Carlo simulations. The framework uniquely bridges deterministic stress analysis and probabilistic risk assessment, enabling systematic evaluation of slip risk under variable geomechanical conditions. An extended parametric study investigates the effects of fault friction correlation length, initial stress anisotropy, deconfinement rate, and tunnel size. Probabilistic results, including minimum safety factors and slip lengths, demonstrate the limitations of deterministic fault stability analysis due to friction angle variability, highlighting the need for spatial randomness in risk-informed tunnel design through faulted rock. The proposed framework supports more reliable excavation strategies in heterogeneous fault environments, advancing safety in tunneling engineering.